Political risk mitigation at MTN. - Siyaya, Muzi Bekithemba. (My University, 2014)
ABSTRACT The purpose of this study is to investigate how MTN has mitigated political risk in foreign markets. Firms expanding into foreign markets encounter political risk in host countries, which if poorly managed, may affect a firm’s profitability and continued operation in the host country (Schmidt, 1986). It follows therefore, that when a firm chooses to enter a foreign market, its political risk exposure should be proactively assessed and managed (Alon & Herbert, 2009). Nevertheless, in spite of the critical importance of political risk in international business, limited attention has been devoted to literature analysing the subject (Busse & Hefeker, 2007). The study employed a qualitative exploratory single case study of Mobile Telephone Networks (MTN). MTN is a successful South African based emerging multinational corporation with significant exposure to countries with high political risk (Fitch Research, 2013). A conceptual framework created from the academic literature review is introduced in figure 3. The framework integrates some of the critical theoretical elements that define the behaviour of a multinational corporation in foreign markets. The findings emanating from the study indicate that political risk in foreign markets increases considerably for multinational corporations operating in regulated sectors. Furthermore, the study demonstrates that by including local private and public capital as equity shareholders, multinational corporations operating in emerging markets can mitigate political risk. The study may benefit corporate executives, strategic planners, academics and corporate boards through developing better insights into managing political risk in foreign markets.
MBA 2014
Keywords: International business enterprises -- Management, Risk management.